2021
DOI: 10.3389/fpsyg.2021.632052
|View full text |Cite
|
Sign up to set email alerts
|

Interparental Conflict and Korean Children’s Inhibitory Control: Testing Emotional Insecurity as a Mediator

Abstract: This study examined the association between interparental conflict and inhibitory control of Korean children, and it investigated whether this relationship is mediated by the single latent variable of emotional insecurity or by three dimensions of emotional insecurity (i.e., involvement, emotional reactivity, and avoidance). A total of 166 mother–father dyads with Korean children aged 3–5 years participated in a short-term longitudinal survey at two-time points. Both parents completed measures of interparental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Additionally, family factors in Korean culture require particular attention because the relationship between parents and children is highly valued owing to the practice of Confucianism ( 13 ), which has been influencing hierarchical relationships between parents and children. Korean children are expected to obey their parents, and Korean parents are more involved in the lives of their children than American parents ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, family factors in Korean culture require particular attention because the relationship between parents and children is highly valued owing to the practice of Confucianism ( 13 ), which has been influencing hierarchical relationships between parents and children. Korean children are expected to obey their parents, and Korean parents are more involved in the lives of their children than American parents ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children may lose their self‐esteem by losing control over their environment and emotions in the event of interparental conflict that they cannot manage independently. As part of emotional insecurity responses, involvement can help buffer the impact of threats by providing a sense of control over conflict; however, the sense of control can be short lived (Lee & Seo, 2021; Mueller et al, 2015). This study shows that children who display involvement responses during interparental conflict may perceive the behavior as being a self‐protective response on losing their sense of control when they reach adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Davies and Martin (2013) suggested that individual differences in the way security systems operate in the context of interparental conflict affect close relationships, such as those with friends and romantic relationships, during early adulthood. To date, many researchers have measured various emotional and behavioral responses that appear when children's developmental goals of emotional security are threatened in interparental conflict, and found that these responses can affect children's problem behaviors at the time of interparental conflict or within a period of 5 years (Cummings et al, 2012; Davies et al, 2014; Davies et al, 2021; Lee & Seo, 2021; Schermerhorn et al, 2021). However, to this author's knowledge, no empirical study has examined how emotional insecurity in interparental conflict affects the offspring's marital conflict (Davies et al, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Gustafsson and colleagues (Gustafsson et al, 2013(Gustafsson et al, , 2015 revealed that American preschool children exposed to a poor interparental relationship between 2 and 3 years tend to display low levels of executive function ability, including working memory, inhibitory control, and cognitive flexibility at 5 years old. In a short-term longitudinal study, Lee and Seo (2021) found that Korean parents who experienced a poor marital relationship when their children were 3-5 years old were more likely to report executive function difficulties in their children 6 months later. In contrast, interparental relationship adjustment has been shown to be positively correlated with children's executive function capabilities (Bridgett et al, 2015;Planalp et al, 2019).…”
Section: Mediating Effect Of Child Executive Functionmentioning
confidence: 99%
“…We selected a 5‐months period because children were typically followed up at the interval between 3 and 9 months in previous short‐term longitudinal studies with preschool samples (Hindman et al, 2011; Karlsson et al, 2018). In addition, a study has indicated that this period is useful in tracing the short‐term effect of interparental marital relationship on early child development (Lee & Seo, 2021). We expected that mother‐reported marital adjustment would positively predict preschool children's prosocial behavior 5 months later.…”
Section: Introductionmentioning
confidence: 99%